Comparative study of blood parameters among widal positive and negative cases of enteric fever in a tertiary care teaching hospital in Maharashtra, India - Soni, Pravin N.; Soni, Seema P.; Ambekar, prakash A. (International Journal of Advances in Medicine, 2017)
Background: Enteric fever is very common and serious infectious disease in tropical country like India. There is need for research in prognosis of enteric fever on the basis of locality of patient’s i.e. urban or rural area. Also, there is scope for research on fever on the basis of OPD (out patient department) or IPD (In patient department) setting. Methods: We have taken widal positive and negative cases from January to December 2014 and they were compared on the hematological and prognostic parameters. Widal positive cases were grouped into IPD and OPD cases as well as those hailing from rural and urban area. These were also compared on the hematological and prognostic parameters. Results: Widal positive group has significantly higher leucocyte count than widal negative group. Also, widal positive group has more chances of having neutrophilia than widal negative group. Lymphocytes were higher in widal negative group. It is also found that lymphocyte count was significantly lower in widal positive group. We got more platelet count in widal positive cases. We compared IPD versus OPD patients; it was found that IPD patients took lesser time for fever to subside. There was no significant difference in fever duration at admission and duration of fever to subside. Conclusions: IPD care is better than OPD care in enteric patients. Apart from leukocyte count, haemoglobin and platelet count in enteric fever should be analyzed in enteric fever.